Modified nano zero-valent iron material and preparation method thereof
Patent Information
- Application Number
- CN202410195939.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-02-22
AI Technical Summary
[0004]本发明的目的在于提供一种改性纳米零价铁材料及其制备方法,以解决现有技术中使用纳米零价铁对重金属污染土壤修复率不高的问题
[0032]本发明提供了一种改性纳米零价铁材料,制备方法简单;在制备纳米零价铁材料的过程中,添加酸改性麦饭石,酸改性清除了麦饭石孔道内的杂质,疏通内部孔道,提高麦饭石对Fe2+的吸附能力,从而可以为纳米零价铁的负载提供更多的负载点位;酸改性麦饭石对Cd有吸附作用,也能增加纳米零价铁附近的Cd浓度,促进纳米零价铁材料与Cd的还原、吸附以及共沉淀作用,加速纳米零价铁对Cd的去除;添加壳聚糖和十二醛,对改性纳米零价铁材料中Fe的溶出有抑制作用,可以提高改性纳米零价铁材料的稳定性。本发明制备的改性纳米零价铁材料可以降低土壤中Cd的生物可利用性,削弱有毒物质向食物链迁移,在重金属污染土壤的修复中起核心作用。
Smart Images

Figure CN118180373B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of heavy metal pollution remediation, specifically relating to a modified nano-zero-valent iron material and its preparation method. Background Technology
[0002] Cadmium is one of the main heavy metal pollutants in farmland soil, with an exceedance rate of 7.0%. Cadmium is extremely active in the migration and transformation of farmland soil-plant system, which not only seriously affects soil structure and function, but also accumulates in food crops such as rice and wheat, and through the food chain, it affects the human liver, kidneys and musculoskeletal system, posing a potential threat to human health.
[0003] Nano-zero-valent iron (NZFI) has shown great potential in addressing heavy metal pollution in soil due to its advantages such as large specific surface area, high surface activity, and strong reducing activity. NZFI can reduce the bioavailability of heavy metal pollutants such as chromium, lead, and cadmium in soil through passivation, weakening the migration of toxic substances into the food chain, and playing a central role in the remediation of heavy metal-contaminated soil. However, due to van der Waals forces, high surface energy, and magnetic effects, NZFI particles introduced into the environment are prone to aggregation or oxidation, severely limiting their widespread application in practical soil pollution remediation. Summary of the Invention
[0004] The purpose of this invention is to provide a modified nano-zero valent iron material and its preparation method, so as to solve the problem that the remediation rate of heavy metal contaminated soil using nano-zero valent iron in the prior art is not high.
[0005] To solve the above-mentioned technical problems, the present invention specifically provides the following technical solution: A modified nano-zero-valent iron material comprises: nano-zero-valent iron and acid-modified maifanite; the nano-zero-valent iron is coated on the surface of the acid-modified maifanite; the nano-zero-valent iron is composed of Fe 2+ Solution reduction yielded; acid-modified maifanite and Fe 2+ The solution volume ratio is 10-120 g:1 mol. Maifan stone has many pores and internal channels on its surface, exhibiting a porous, sponge-like structure. Acid modification removes impurities from the pores of the maifan stone, unblocks the internal channels, and improves the maifan stone's resistance to Fe. 2+ The adsorption capacity of the nano-zero valent iron provides more loading sites for the nano-zero valent iron; acid-modified maifanite has an adsorption effect on Cd and can also increase the Cd concentration near the nano-zero valent iron, promote the reduction, adsorption and co-precipitation of nano-zero valent iron material and Cd, and accelerate the removal of Cd by nano-zero valent iron; it can also promote the formation of iron film on the root surface of rice and limit the migration of Cd into the plant.
[0006] Preferably, the preparation method of acid-modified maifan stone is as follows: maifan stone is ground to obtain maifan stone powder, the maifan stone powder is soaked in an acid solution, washed, and dried to obtain acid-modified maifan stone.
[0007] Preferably, the maifan stone is placed in an agate cup, grinding balls are added, and a planetary ball mill is used for grinding.
[0008] Preferably, the diameter of the grinding ball is 1-10 mm.
[0009] Preferably, the grinding speed is 200-400 r / min.
[0010] Preferably, the acid solution includes a sulfuric acid solution.
[0011] Preferably, the soaking time is 3-5 hours.
[0012] Preferably, the washing is performed with ultrapure water until the solution is neutral.
[0013] Preferably, the drying temperature is 50-60℃.
[0014] Preferably, the preparation method of the modified nano-zero-valent iron material is as follows: preparing Fe 2+ Acid-modified maifanite was added to the solution, and the mixture was ultrasonicated and stirred to obtain acid-modified maifanite complexed Fe. 2+ The solution was reacted by adding a reducing agent dropwise. After the reaction was completed, the solid particles were separated, washed, and dried to obtain the modified nano-zero-valent iron material.
[0015] Preferably, the reducing agent includes a sodium borohydride solution.
[0016] Preferably, the ultrasound conditions are 20-40 minutes at room temperature.
[0017] Preferably, the stirring conditions are stirring at a speed of 400-600 rpm for 10-14 h.
[0018] Preferably, the dripping rate is 1-2 drop / s.
[0019] Preferably, the separation is achieved by using a magnet to attract and separate the solid particles. Preferably, the washing involves alternately washing the separated solid particles with deoxygenated water and deoxyethanol.
[0020] In one embodiment, the method for preparing acid-modified maifanite is as follows: Weigh out maifan stone by weight and place it in an agate cup. Add grinding balls and grind the maifan stone in a planetary ball mill. After grinding, obtain maifan stone powder and store it in a desiccator. Wash the maifan stone powder in ultrapure water, soak it in sulfuric acid solution, wash it with ultrapure water until neutral, and dry it to obtain acid-modified maifan stone.
[0021] Preferably, the maifanite is present in 50-100 parts by weight.
[0022] Preferably, the amount of maifanite powder is 20-30 parts by weight.
[0023] Preferably, the sulfuric acid solution has a weight of 40-60 parts and a concentration of 1.0-2.5 mol / L.
[0024] In one implementation scheme, the method for preparing the modified nano-zero-valent iron material is as follows: By weight, FeSO4·7H2O was dissolved in deoxygenated water to prepare a FeSO4·7H2O solution. Acid-modified maifanite was added to the FeSO4·7H2O solution, and the mixture was ultrasonicated and stirred at room temperature to obtain acid-modified maifanite complexed Fe. 2+ Solution; complexing Fe with acid-modified maifanite 2+ Sodium borohydride solution was added dropwise to the solution. After the sodium borohydride solution was completely added, the reaction was allowed to proceed fully. The entire process was carried out under N2 protection. The black solid particles were separated by attracting them with a magnet, and the particles were washed alternately with deoxygenated water and deoxyethanol. The particles were then placed in a vacuum freeze dryer until completely dry to obtain modified nano-zero-valent iron material.
[0025] Preferably, the FeSO4·7H2O solution has a weight of 200-400 parts and a concentration of 0.1-0.2 mol / L.
[0026] Preferably, the acid-modified maifanite is 0.1-3 parts by weight.
[0027] Preferably, the sodium borohydride solution has a weight of 200-500 parts and a concentration of 0.1-0.3 mol / L.
[0028] In one implementation scheme, the method for preparing the modified nano-zero-valent iron material is as follows: FeSO4·7H2O solution was prepared by dissolving FeSO4·7H2O in deoxygenated water by weight. Chitosan solution was prepared by dissolving chitosan in HNO3 solution. Chitosan solution and dodecylaldehyde were added to the FeSO4·7H2O solution, the pH was adjusted to acidic, stirred, and sodium borohydride solution was added dropwise. After the reaction, the pH of the reaction solution was adjusted to alkaline, acid-modified maifanite was added, and the mixture was sonicated and stirred. The entire process was carried out under N2 protection. The black solid particles were separated by attraction with a magnet, and the particles were washed several times alternately with deoxygenated water and deoxyethanol. The particles were then placed in a vacuum freeze dryer until completely dried to obtain modified nano-zero valent iron material. The addition of chitosan and dodecylaldehyde inhibited the dissolution of Fe in the modified nano-zero valent iron material, thereby improving the stability of the nano-zero valent iron solution.
[0029] Preferably, the chitosan content is 0.05-5 parts by weight.
[0030] Preferably, the concentration of the HNO3 solution is 0.05-0.2 mol / L, and the weight is 200-400 parts.
[0031] Preferably, the amount of dodecyl is 0.5-1% of the weight of chitosan.
[0032] This invention provides a modified nano-zero-valent iron material with a simple preparation method. During the preparation of the nano-zero-valent iron material, acid-modified maifanite is added. Acid modification removes impurities from the pores of the maifanite, unblocks the internal channels, and improves the maifanite's ability to resist Fe. 2+ The adsorption capacity of the modified nano-zero-valent iron (NZFE) provides more loading sites for the NZFE nanoparticles. Acid-modified maifanite adsorbs Cd and increases the Cd concentration near the NZFE nanoparticles, promoting the reduction, adsorption, and co-precipitation of Cd by the NZFE nanoparticles, thus accelerating the removal of Cd by the NZFE nanoparticles. The addition of chitosan and dodecyl aldehyde inhibits the dissolution of Fe from the modified NZFE nanoparticles, improving their stability. The modified NZFE nanoparticles prepared in this invention can reduce the bioavailability of Cd in soil, weaken the migration of toxic substances into the food chain, and play a crucial role in the remediation of heavy metal-contaminated soils. Attached Figure Description
[0033] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.
[0034] Figure 1 The graph shows the Cd content of rice grains in different embodiments and comparative examples. Detailed Implementation
[0035] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.
[0036] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0037] Example 1: A modified nano-zero-valent iron material and its preparation method S1, Preparation of acid-modified maifanite Weigh 50 g of maifan stone and place it in an agate cup. Add grinding balls with diameters of 3, 5, and 8 mm, and grind in a planetary ball mill at 300 r / min from two directions for 12 h. After ball milling, obtain maifan stone powder and store it in a desiccator. Wash 25 g of maifan stone powder in ultrapure water to remove impurities, soak it in 50 mL of 2.5 mol / L sulfuric acid solution for 4 h, then wash with ultrapure water until neutral, and dry at 50℃ to obtain acid-modified maifan stone.
[0038] S2, Preparation of modified nano-zero-valent iron materials FeSO4·7H2O was dissolved in deoxygenated water to prepare a 200 mL solution with a concentration of 0.1 mol / L. 0.28 g of acid-modified maifanite was added to the mixture, and the solution was sonicated at room temperature for 30 min, followed by stirring at 500 rpm for 12 h to obtain acid-modified maifanite complexed Fe. 2+ Solution; complexing Fe with acid-modified maifanite 2+ 250 mL of a 0.2 mol / L sodium borohydride solution was added dropwise to the solution at a rate of 1 drop / s. After the sodium borohydride solution was completely added, the mixture was stirred for 30 min to allow the reaction to proceed fully. The entire process was carried out under N2 protection. The black solid particles were separated by attracting them with a magnet and washed several times alternately with deoxygenated water and deoxyethanol. The particles were then placed in a vacuum freeze dryer until completely dry to obtain modified nano-zero valent iron material.
[0039] Example 2: A modified nano-zero-valent iron material and its preparation method S1, Preparation of acid-modified maifanite, same as in Example 1.
[0040] S2, unlike Example 1, keeps other reaction conditions constant, but changes the mass of acid-modified maifanite to 0.56 g, so that the acid-modified maifanite reacts with Fe... 2+ The mass ratios were 1:2, and modified nano-zero-valent iron materials were synthesized.
[0041] Example 3: A modified nano-zero-valent iron material and its preparation method S1, Preparation of acid-modified maifanite, same as in Example 1.
[0042] S2, Preparation of modified nano-zero-valent iron materials Unlike Example 1, other reaction conditions were kept constant, but the mass of acid-modified maifanite was changed to 1.12 g, so that the acid-modified maifanite reacted with Fe... 2+ The mass ratios were 1:1, and modified nano-zero-valent iron materials were synthesized.
[0043] Example 4: A modified nano-zero-valent iron material and its preparation method S1, Preparation of acid-modified maifanite, same as in Example 1.
[0044] S2, Preparation of modified nano-zero-valent iron materials Unlike Example 1, other reaction conditions were kept constant, but the mass of acid-modified maifanite was changed to 2.24 g, so that the acid-modified maifanite reacted with Fe... 2+ The mass ratios were 2:1, and modified nano-zero-valent iron materials were synthesized.
[0045] Example 5: A modified nano-zero-valent iron material and its preparation method S1, Preparation of acid-modified maifanite Weigh 50 g of maifan stone and place it in an agate cup. Add grinding balls with diameters of 3, 5 and 8 mm. Grind the maifan stone in a planetary ball mill at a speed of 300 r / min from two directions for 12 h. Dry the ball-milled maifan stone in an oven at 80℃ to obtain maifan stone powder and store it in a desiccator.
[0046] 25 g of maifan stone powder was washed clean in ultrapure water to remove impurities, then soaked in 50 mL of 2.5 mol / L sulfuric acid solution for 4 h, and then washed with ultrapure water until neutral. The powder was dried at 50 °C to obtain acid-modified maifan stone.
[0047] S2, Preparation of modified nano-zero-valent iron materials FeSO4·7H2O was dissolved in deoxygenated water to prepare 200 mL of 0.1 mol / L FeSO4·7H2O solution; 0.05 g of chitosan was dissolved in 200 mL of 0.1 mol / L HNO3 solution to prepare chitosan solution; chitosan solution and dodecylaldehyde were added to the FeSO4·7H2O solution, with the total amount of dodecylaldehyde being 0.5% of the chitosan mass, the pH was adjusted to 5.0, and the mixture was stirred for 5 h. 500 mL of 0.2 mol / L sodium borohydride solution was added dropwise at a rate of 1 drop / s. After reacting for 15 h, the pH of the reaction solution was adjusted to 10, 2.24 g of acid-modified maifanite was added, and the mixture was sonicated at room temperature for 30 min, followed by stirring at 500 rpm for 12 h. The entire process was carried out under N2 protection. The black solid particles were attracted and separated by a magnet, and the particles were washed several times with deoxygenated water and deoxyethanol alternately. The particles were then placed in a vacuum freeze dryer until completely dried to obtain modified nano-zero valent iron material.
[0048] Example 6: A modified nano-zero-valent iron material and its preparation method S1, Preparation of acid-modified maifanite, same as in Example 1.
[0049] S2, Preparation of modified nano-zero valent iron material, differs from Example 5 in that other reaction conditions are kept unchanged, but the amount of chitosan is changed to 0.5 g.
[0050] Example 7: A modified nano-zero-valent iron material and its preparation method S1, Preparation of acid-modified maifanite, same as in Example 1.
[0051] S2, Preparation of modified nano-zero-valent iron material, differs from Example 5 in that other reaction conditions are kept unchanged, but the amount of chitosan is changed to 5 g.
[0052] Comparative Example 1: A nanomaterial of zero-valent iron and its preparation method Acid-modified maifanite complexed with FeSO4·7H2O was prepared by dissolving FeSO4·7H2O in deoxygenated water to prepare 200 mL of 0.1 mol / L FeSO4·7H2O solution. 2.24 g of maifanite was added to the mixture, and the solution was sonicated at room temperature for 30 min, followed by stirring at 500 rpm for 12 h. 2+ Solution; complexing Fe with acid-modified maifanite 2+ 250 mL of a 0.2 mol / L sodium borohydride solution was added dropwise to the solution at a rate of 1 drop / s. After the sodium borohydride solution was completely added, the mixture was stirred for 30 min to allow the reaction to proceed fully. The entire process was carried out under N2 protection. The black solid particles were separated by attracting them with a magnet and washed several times alternately with deoxygenated water and deoxyethanol. The particles were then placed in a vacuum freeze dryer until completely dry to obtain the modified nano-zero valent iron material.
[0053] Experimental Example 1: 1. Pot experiment 1.1 Sample Modified nano-zero-valent iron materials of Examples 1-7 and unmodified nano-zero-valent iron materials of Comparative Example 1.
[0054] 1.2 Methods Using Zhejing 100 as the test organism, a pot experiment was conducted to compare and study the rice yield and grain metabolite composition in Cd-contaminated soil under the influence of unmodified nano-zero-valent iron materials in Comparative Example 1 and modified nano-zero-valent iron materials in Examples 1-7. The total iron content of the modified nano-zero-valent iron materials in Examples 1-7 was determined to be 58.5% by flame atomic absorption spectrometry. The Cd concentration in each group was 20 mg / kg. Considering that the iron content in the modified nano-zero-valent iron materials in Examples 1-7 was 58.5%, the treatment settings were as follows: modified nano-zero-valent iron material treatment group in Examples 1-7 (1000 mg / kg), unmodified nano-zero-valent iron material treatment group in Comparative Example 1 (585 mg / kg). The nano-zero-valent iron and other remediation materials were uniformly dispersed in the soil by stepwise dilution to achieve the concentration set in the experiment; Cd... 2+ The CdCl2 solution was injected into the soil and stirred thoroughly. Each treatment contained 3.5 kg of dry soil, and the experiment was set up in triplicate, with each parallel containing 3 rice plants. During the experiment, the liquid level in the pots was kept 1-3 cm above the soil. Rice grains were collected during the grain-filling stage, flash-frozen in liquid nitrogen, and stored at -80℃ for metabolomics analysis. After harvesting the rice at 140 days, the grain weight was recorded, and the Cd content in the grains was analyzed. The method for determining the Cd content in rice grains was based on the national standard "National Food Safety Standard - Determination of Cadmium in Food" (GB5009.15-2014). After the mature grains were cold-dried, dehulled, and ground, 0.5 g was weighed into a digestion tube, and 5 mL of HNO3 and 2 mL of H2O2 were added. The digestion was carried out using a microwave digester. After acid removal and volume adjustment, the Cd content was determined by ICP-MS. The results are shown below. Figure 1 As shown.
[0055] Figure 1 The graph shows the Cd content of rice grains in different embodiments and comparative examples, from... Figure 1It can be seen that the modified nano-zero-valent iron materials of Examples 1-7 of the present invention significantly inhibited Cd accumulation in rice grains compared with the modified nano-zero-valent iron material of Comparative Example 1. This indicates that without the addition of acid-modified maifanite and / or chitosan during the synthesis of modified nano-zero-valent iron, the formation of an iron film on the rice root surface cannot be promoted, allowing Cd to migrate into the plant interior, resulting in a lack of significant inhibition of Cd accumulation in rice grains. The Cd content in the rice grains of Example 2 of the present invention was lower than that in the rice grains of Example 1, indicating that increasing the amount of acid-modified maifanite used increased the loading of the nano-zero-valent iron material and promoted the formation of an iron film on the rice root surface. Membrane formation restricts Cd migration into the plant interior, thus improving the inhibitory effect on Cd accumulation in rice grains. The Cd content in rice grains of Example 3 was lower than that of Example 2, indicating that increasing the amount of acid-modified maifanite improved the loading of nano-zero-valent iron, thereby increasing the inhibition of Cd accumulation in rice grains. The Cd content in rice grains of Example 4 was lower than that of Example 3, indicating that with the continuous increase of the proportion of acid-modified maifanite, the acidic maifanite adsorbed Cd, increasing the Cd concentration near the nano-zero-valent iron. This reduces the bioavailability of Cd in the soil, weakens the migration of toxic substances into the food chain, and gradually increases the inhibition of Cd accumulation in rice grains. The Cd content in rice grains of Example 5 of this invention is lower than that of rice grains of Example 4, indicating that the addition of chitosan and dodecyl aldehyde during the synthesis of modified nano-zero-valent iron can improve the dispersion stability of the modified nano-zero-valent iron material particles, increase the reactivity of nano-zero-valent iron, promote the formation of an iron film on the rice root surface, limit the migration of Cd into the plant interior, and reduce the accumulation of Cd in rice grains. The Cd content in rice grains of Example 6 of this invention is low. The Cd content in rice grains in Example 5 demonstrates that increasing the amount of chitosan and dodecylaldehyde added during the synthesis of modified nano-zero valent iron can improve the stability of the particle dispersion of the modified nano-zero valent iron material and enhance the inhibition of Cd accumulation in rice grains by nano-zero valent iron. The Cd content in rice grains in Example 7 of this invention is lower than that in rice grains in Example 6, indicating that during the synthesis of modified nano-zero valent iron, as the proportion of chitosan and dodecylaldehyde added continuously increases, the bioavailability of Cd in the soil is reduced, the migration of toxic substances into the food chain is weakened, and the accumulation of Cd in rice grains is reduced.
[0056] 2. Stability Test 2.1 Sample Modified nano-zero-valent iron materials of Examples 1-7 and unmodified nano-zero-valent iron materials of Comparative Example 1.
[0057] 2.2 Methods Determination of metal dissolution rate: 50 mL of nitrobenzene wastewater with an initial concentration of 25 mg / L was added to an Erlenmeyer flask. Modified nano-zero-valent iron materials from Examples 1-7 and unmodified nano-zero-valent iron materials from Comparative Example 1 were added at a dosage of 4.0 g / L. The pH was adjusted to 7, the temperature was 25℃, and the reaction was carried out at a constant temperature with an oscillation rate of 300 r / min for 60 min. Samples were taken to determine the dissolution rate of Fe metal in the solution. An Agilent 7700s inductively coupled plasma optical emission spectrometer (ICP-OES) was used to analyze the metal precipitation of the composite material in the solution after the reaction.
[0058] Table 2 Fe metal leaching rate (%) in different embodiments and comparative examples
[0059] As shown in Table 2, the modified nano-zero-valent iron materials of Examples 1-7 of the present invention have stronger stability than the modified nano-zero-valent iron material of Comparative Example 1, indicating that without the addition of acid-modified maifanite and / or chitosan during the synthesis of modified nano-zero-valent iron, the synthesized modified nano-zero-valent iron material has poor stability. The Fe dissolution rate of the modified nano-zero-valent iron material of Example 2 of the present invention is lower than that of Example 1, indicating that increasing the amount of acid-modified maifanite can improve the stability of the modified nano-zero-valent iron. The Fe dissolution rate of the modified nano-zero-valent iron material of Example 3 of the present invention is lower than that of Example 2, indicating that increasing the amount of acid-modified maifanite further improves the stability of the modified nano-zero-valent iron. The Fe dissolution rate of the modified nano-zero-valent iron material of Example 4 is lower than that of Example 3, indicating that with the increase of the amount of acid-modified maifanite, the stability of the modified nano-zero-valent iron is further improved. The stability of modified nano-zero valent iron is improved. The Fe dissolution rate of the modified nano-zero valent iron material in Example 5 of this invention is lower than that of the modified nano-zero valent iron liquid sample prepared in Example 4, indicating that the addition of chitosan and dodecaldehyde during the synthesis of modified nano-zero valent iron inhibits the dissolution of Fe in the modified nano-zero valent iron material. The Fe dissolution rate of the modified nano-zero valent iron material in Example 6 of this invention is lower than that in Example 5, indicating that increasing the amount of chitosan and dodecaldehyde during the synthesis of modified nano-zero valent iron effectively inhibits the dissolution of Fe in the nano-zero valent iron material. The Fe dissolution rate of the modified nano-zero valent iron material in Example 7 of this invention is lower than that in Example 6, indicating that further increasing the amount of chitosan and dodecaldehyde inhibits the dissolution of metallic Fe in the modified nano-zero valent iron material, thus improving the material stability.
[0060] The conventional operations in the operation steps of this invention are well known to those skilled in the art and will not be described in detail here.
[0061] The embodiments described above provide a detailed explanation of the technical solution of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, additions, or similar substitutions made within the scope of the principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A modified nanomaterial of zero-valent iron, comprising: Nano-zero valent iron and acid-modified maifanite; The nano-zero-valent iron is coated on the surface of the acid-modified maifanite; The nano-zero-valent iron is composed of Fe 2+ The solution was reduced to obtain the acid-modified maifanite and Fe. 2+ The volume ratio of the solution used is 10-120 g: 1 mol; The preparation method of the modified nano-zero-valent iron material is as follows: Fe is prepared... 2+ Acid-modified maifanite was added to the solution, and the mixture was ultrasonicated and stirred to obtain acid-modified maifanite complexed Fe. 2+ A solution was subjected to a reaction by adding a reducing agent dropwise. After the reaction was completed, the solid particles were separated, washed, and dried to obtain modified nano-zero-valent iron material. The reducing agent included sodium borohydride solution. The Fe 2+ The solution includes a chitosan solution and dodecylaldehyde, wherein the chitosan solution comprises chitosan and HNO3 solution.
2. The modified nano-zero-valent iron material according to claim 1, characterized in that, The preparation method of the acid-modified maifan stone is as follows: maifan stone is ground to obtain maifan stone powder, the maifan stone powder is soaked in an acid solution, washed, and dried to obtain acid-modified maifan stone.
3. The modified nano-zero-valent iron material according to claim 2, characterized in that, The grinding process involves placing maifan stone into an agate cup, adding grinding balls, and grinding using a planetary ball mill; the diameter of the grinding balls is 1-10 mm; and the grinding speed is 200-400 r / min.
4. The modified nano-zero-valent iron material according to claim 2, characterized in that, The acid solution includes a sulfuric acid solution; the soaking time is 3-5 hours; the washing is done with ultrapure water until neutral; and the drying temperature is 50-60°C.
5. The modified nano-zero-valent iron material according to claim 1, characterized in that, The ultrasonic conditions are 20-40 min at room temperature; the stirring conditions are 400-600 rpm for 10-14 h.
6. The modified nano-zero-valent iron material according to claim 1, characterized in that, The dripping rate is 1-2 drops / s.
7. The modified nano-zero-valent iron material according to claim 1, characterized in that, The separation is achieved by using a magnet to attract and separate solid particles; the washing is achieved by alternately washing the separated solid particles with deoxygenated water and deoxyethanol.
Citation Information
Patent Citations
Preparation method and application of nanometer zero-valent ion composite material
CN106745645A
Reagent and method for reducing heavy metal pollution of Chinese herbal medicine
CN113290038A